STRATEGI DAKWAH TUAN GURU SUJARMAN DALAM MENINGKATKAN KEAGAMAAN MASYARAKAT (Studi Kasus Di Dusun Kelambi Desa Pandan Indah) - Rohimi Rohimi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
Da'wah is a form of Islamic mission in spreading and teaching religion, and preaching is carried out or delivered by ulama and preachers to convey Islamic teachings to the public. And in this study, examines the da'wah strategy represented by one of the Guru Teachers and Sujarman Teachers who carry out Islamic da'wah in Kelambi Hamlet, Pandan Indah Village. In this study, researchers used a qualitative method by plunging into the research location in Kelambi Hamlet, Pandan Indah Village. And the data collection process in this study was carried out with several methods, namely the method of interviewing, observing, and documenting. The results and discussion agreed in this study on the da'wah strategy carried out by Mr. Guru Sujarman viz. First, discussing da'wah through early childhood, with the delivery of da'wah material related to Islamic learning and short lectures on the religion of Islam. Second, related to propaganda through the public or adult society, with the delivery of propaganda material related to the (special) and (general). For example, specifically for requesting pilgrims and Koran books of Fikh. While the general ones such as the lecture of spiritual splash and evening remembrance on Friday. However, in every preaching action carried out, of course what must be done against preaching is done, for example in the preaching of Master Sujarman carried out in Kelambi Hamlet, increasing community support in discussing Islamand helping many people in choosing education who are religious or enter pesantren education.